Membangun Koneksi dengan Generasi Milenial: Strategi Dakwah yang Efektif dalam Era Digital - Surbakti, Muhammad Faizul Akbar; Mutiawati, Mutiawati; Ritonga, Hasnun Jauhari (Lembaga Yasin AlSys, 2023)
This study aims to analyze effective da'wah strategies in building connections with the millennial generation in the digital era. The millennial generation has different characteristics and communication preferences compared to the previous generation, therefore, it is necessary to have the right approach in conveying da'wah messages to them. In this research, we explore various da'wah strategies that are effective in building connections with the millennial generation and identify the factors that influence the success of these da'wah strategies. This study uses a qualitative approach involving in-depth interviews and analysis of social media content as a data collection method. It is hoped that the results of this research will be able to provide valuable insights for da'wah activists, especially in facing challenges and opportunities in interacting with the millennial generation in the digital era.